Constructing My Cultural Identity: A Reflection on the Contradictions, Dilemmas, and Reality - Neegan, Erica (Alberta Journal of Educational Research, 2008)
This article provides a critical reflective analysis of my life growing up in Jamaica where I attended colonial school, to making the transition to high school in the Canadian context. I examine the elements that have influenced my cultural/racial identity as a person of African ancestry living in the diaspora. I ask questions such as how has colonial education influenced my cultural identity and how I see myself? I address the complexity of my racial and gender identity drawing on a Black feminist theoretical framework and anticolonial thought to inform this work.